Why do wolves eat livestock?: Factors influencing wolf diet in northern Italy - Imbert, Camille; Caniglia, Romolo; Fabbri, Elena; MILANESI, PIETRO; Randi, Ettore; Serafini, Matteo; Torretta, Elisa; MERIGGI, ALBERTO (Biological Conservation, 2016)
Thanks to protection by law and increasing habitat restoration, wolves (Canis lupus) are currently re-colonizing Europe fromthe surviving populations of Russia, the Balkan countries, Spain and Italy, raising the need to update conservation strategies. A major conservation issue is to restore connections and gene flow among fragmented populations, thus contrasting the deleterious consequences of isolation. Wolves in Italy are expanding from the Apennines towards the Alps, crossing the Ligurian Mountains (northern Italy) and establishing connections with the Dinaric populations. Wolf expansion is threatened by poaching and incidental killings, mainly due to livestock depredations and conflicts with shepherds, which could limit the establishment of stable populations. Aiming to find out the factors affecting the use of livestock by wolves, in this study we determined the composition of wolf diet in Liguria. We examined 1457 scats collected from 2008 to 2013. Individual scats were genotyped using a non-invasive genetic procedure, and their content was determined using microscopical analyses. Wolves in Liguria consumed mainly wild ungulates (64.4%; in particular wild boar Sus scrofa and roe deer Capreolus capreolus) and, to a lesser extent, livestock (26.3%; in particular goats Capra hircus). We modeled the consumption of livestock using environmental features, wild ungulate community diversity, husbandry characteristics and wolf social organization (stable packs or dispersing individuals).Wolf diet varied according to years and seasons with an overall decrease of livestock and an increase ofwild ungulate consumption, but also between packs and dispersing individuals with greater livestock consumption for the latter. The presence of stable packs, instead of dispersing wolves, the adoption of prevention measures on pastures, roe deer abundance, and the percentage of deciduous woods, reduced predation on livestock. Thus, we suggest promoting wild ungulate expansion, the use of prevention tools in pastures, and ...